ANALYSIS OF e-INVOICE IMPLEMENTATION IN INPUT TAX CONTROL: (Case Study at PT.TT Metals Indonesia) - Nurdiansyah, Dian Hakip; Nawawi, Ahmad; Kosasih, Kosasih; Sundamanik, Siti Jamilah (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2021)
The purpose of analyzing the application of e-invoice in controlling tax credit input of PT. TT Metals Indonesia, the obstacles that occur and how to overcome the obstacles in the implementation of Electronic Tax Invoice in control in an effort to prevent the issuance of fictitious tax invoices. Researcher method uses qualitative research with descriptive analysis. The results of this study are that PT. TT Metals Indonesia Karawang in the percentage that before the occurrence of tax invoices in 2013 amounted to 0.92% while after the Tax Invoice in 2015 amounted to 0.05% shows that experiencing a decrease in losses due to input tax correction before and after the application of e-invoice. Constraints that arise during the application of the Electronic Tax Invoice are dependence on the system and internet network connection, the inadequate level of ability and negligence of the Taxable Entrepreneur and the Taxable Entrepreneur computer facility, while the alternative way to overcome the obstacles that arise during the application of the Electronic Tax Invoice is through an increase the quality of the information system network, and appeals to Taxable Entrepreneurs to update the computer.